Effect of age on contrast sensitivity function: uniocular and binocular findings. - J E Ross; David D. Clarke; Anthony J. Bron (1985)
Monocular and binocular contrast sensitivity function for a range of spatial frequencies was measured in two groups of subjects with normal vision. Statistically significant differences in performance between the younger group (age 20-30 years) and the older group (age 50-87 years) were found at all spatial frequencies sampled between 0.40 and 19 X 25 cpd. In the age range 50-87 years there was a linear decline in contrast sensitivity with age for medium and high spatial frequencies, but sensitivity for low spatial frequencies was independent of age.